1999
DOI: 10.2134/agronj1999.915845x
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Solar Irradiance for Crop Modeling Using Daily Air Temperature Data

Abstract: stricting their application in retrospective or validation studies (Hutchinson, 1991). Crop growth models require solar irradiance as input data, yetThe need for solar irradiance data for crop models there are few places where such data are routinely measured. For has led researchers to develop a number of methods for locations where measured values are not available, solar irradiance simulating such data. For example, some crop modelers can be estimated using empirical models such as the Bristow-(e.g., Rosent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
76
0
14

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(93 citation statements)
references
References 14 publications
1
76
0
14
Order By: Relevance
“…Figure 2 shows the correlation behavior of these two models at the weather station of the municipality of Sinop. In this case, due to temporal partition, these values were lower than those found by Goodin (1999) in the United States and by Silva et al (2012) under the climatic conditions of the state of Minas Gerais, but were similar to those reported by Liu et al (2009) and Almorox et al (2011) under the climatic conditions of China and Spain, respectively.…”
Section: Resultssupporting
confidence: 72%
See 2 more Smart Citations
“…Figure 2 shows the correlation behavior of these two models at the weather station of the municipality of Sinop. In this case, due to temporal partition, these values were lower than those found by Goodin (1999) in the United States and by Silva et al (2012) under the climatic conditions of the state of Minas Gerais, but were similar to those reported by Liu et al (2009) and Almorox et al (2011) under the climatic conditions of China and Spain, respectively.…”
Section: Resultssupporting
confidence: 72%
“…The best statistical performance in estimating the global radiation for the state of Mato Grosso, Brazil, is obtained by the Bristow & Campbell (1984) and Goodin et al (1999) models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although empirically derived and conceptually simple, air temperature-based empirical models are founded on theoretical concepts for energy exchange on the surface boundary layer (Goodin et al, 1999). These models are based on the assumptions that (a) clear skies will increase the daily maximum temperature because of the greater short wave radiation input, while resulting in decreased minimum air temperature due to reduced long wave emission from the atmosphere; and (b) cloudy conditions will decrease the daily maximum air temperature due to reduced air transmissivity, while resulting in increased minimum air temperature due to increased long wave radiation from the clouds (Allen, 1997;Donatelli and Campbell, 1998;Almorox et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…These methods are based on empirical modelling related to variables such as temperature Bristow and Campbell, 1984;Donatelli and Campbell, 1998;Goodin et al,1999;Mahmood and Hubbard, 2002;Benghanem and Mellit, 2014), sunshine duration ( Angstrom, 1924;Prescott, 1940;Al-Mostafa et al, 2014;Despotovic et al, 2015;Lockart et al, 2015;Teke et al, 2015), rainfall ( McCaskill, 1990;Liu and Scott, 2001;Chen et al, 2006;Wu et al, 2007;Kirmani et al, 2015), cloudiness ( Supit and van Kappel, 1998;Gu et al, 2001;Badescu, 2002), elevation (Allen, 1995;Winslow et al, 2001;Annandale et al, 2002), humidity (Gu et al, 2001;Chen et al, 2006;Almorox et al, 2011;Li et al, 2013;Antonanzas-Torres et al, 2013;Li et al, 2015) and latitude (Toğrul and Onat, 1999;Skeiker, 2006). Several studies have shown that the best performing models use sunshine duration data, followed by those utilizing cloudiness and then temperature data (Bakirci, 2009;Chen and Li, 2013).…”
Section: Estimation Of Extraterrestrial Radiationmentioning
confidence: 99%